2001
DOI: 10.1006/mthe.2001.0298
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Therapeutic Effect of HSV-tk+GCV Gene Therapy and Ionizing Radiation for Prostate Cancer

Abstract: Standard therapies for prostate cancer including radiation, prostatectomy, and hormone ablation have significant toxicities and recurrence risk. HSV-tk gene therapy may be effective in combination with radiation therapy due to complementary mechanisms and distinct toxicity profiles. Mouse prostate tumors transplanted subcutaneously were treated by either gene therapy involving intratumoral injection of AdV-tk followed by systemic ganciclovir or local radiation therapy or the combination of gene and radiation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 17 publications
3
45
0
Order By: Relevance
“…24 The HSV-TK/GCV system combined with radio-sensitization has been previously studied in non-targeted, locally delivered gene delivery systems. 12,13 However, although a synergistic effect has been demonstrated, this approach ultimately failed to suppress glioblastoma multiforme in a Phase III clinical trial. 2 Endothelial cell apoptosis has been demonstrated to be involved in tumor response to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 The HSV-TK/GCV system combined with radio-sensitization has been previously studied in non-targeted, locally delivered gene delivery systems. 12,13 However, although a synergistic effect has been demonstrated, this approach ultimately failed to suppress glioblastoma multiforme in a Phase III clinical trial. 2 Endothelial cell apoptosis has been demonstrated to be involved in tumor response to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It is hypothesized that the mechanism of this enhanced therapeutic effect is based on the complementing mechanisms of the two therapies. HSV-TK prodrug gene therapy may radiosensitize cells by generating high local concentration of nucleotide analogues, promoting death of cells that might otherwise repair radiation-induced DNA breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that the radiation-induced cellular membrane damage may facilitate the transfer of cytotoxic nucleotide analogs from HSV-tk-expressing cells to neighboring nontransduced cells. This combined approach has been effective in various tumor models 194 and has been shown to delay local tumor growth and prolong survival in a mouse prostate cancer model 195,196 and a mouse mammary tumor model. 197 These results indicate that multiple courses of HSV-TK therapy, in combination with radiation, improve the therapeutic efficacy of this approach and may provide therapeutic implications for the treatment of human breast cancer and other solid tumors.…”
Section: Rationale For Combination Therapymentioning
confidence: 99%
“…It was also demonstrated that the combined therapy had a considerably better antimetastatic effect compared to HSV-tk gene therapy alone; this phenomenon was attributed to the induction of a potent local and systemic immune response, as evidenced by the abundance of CD4 þ cells in the primary tumor. 196,197 Another area likely to be investigated intensely in the coming years is the combination of immunotherapy with established conventional tumor therapies. In this regard, enhancement of antitumor immune response of granulocyte/macrophage-colony stimulating factor-secreting whole cell vaccines in Her-2/neu mice by administration of cyclophosphamide, doxorubicin, or paclitaxel could be demonstrated.…”
Section: Rationale For Combination Therapymentioning
confidence: 99%